Environmental Horticulture: Pathways to Sustainability and Climate Resilience - Vaishnavi Joshi (International Journal of Trends in Horticulture, 2024)
Environmental horticulture represents a multidisciplinary approach that combines plant cultivation, landscape management, and sustainable practices to address pressing global environmental challenges while promoting ecological and societal well-being. This study delves into key themes such as sustainable horticulture, urban agriculture, vertical farming, hydroponics, aquaponics, and their significant contributions to biodiversity conservation, soil and water preservation, and climate change mitigation. The integration of innovative practices like green roofs, living walls, and biophilic design is highlighted, demonstrating their roles in enhancing urban ecosystems, improving air quality, and reducing the urban heat island effect. Furthermore, the paper examines the potential of renewable energy applications and technological advancements in transforming horticultural systems into resource-efficient, climate-resilient models. These practices not only improve ecosystem services, such as carbon sequestration and pollination, but also foster social and economic benefits by supporting urban resilience, rural development, and sustainable livelihood generation. The findings underscore the critical importance of ecological design in addressing urban and rural challenges, bridging traditional horticultural practices with modern technological innovations. Environmental horticulture emerges as a pivotal tool in achieving global sustainability goals by fostering resilience, conserving resources, and harmonizing human activities with the natural environment. This study highlights its transformative potential in mitigating environmental degradation and shaping a sustainable future.
Keywords: Environmental horticulture; Renewable energy; Vertical farming; biodiversity conservation; climate change mitigation; ecosystem services; green roofs; soil conservation; sustainable horticulture; urban agriculture